The Realities of Community Based Natural Resource Management and Biodiversity Conservation in Sub-Saharan Africa - and DeGeorges, Paul Andre; Reilly, Brian Kevin (Sustainability, 2009)
This is an historic overview of conservation in Sub-Saharan Africa from pre-colonial times through the present. It demonstrates that Africans practiced conservation that was ignored by the colonial powers. The colonial market economy combined with the human and livestock population explosion of the 21st century are the major factors contributing to the demise of wildlife and critical habitat. Unique insight is provided into the economics of a representative safari company, something that has not been readily available to Community Based Natural Resources Management (CBNRM) practitioners. Modern attempts at sharing benefits from conservation with rural communities will fail due to the low rural resource to population ratio regardless of the model, combined with the uneven distribution of profits from safari hunting that drives most CBNRM programs, unless these ratios are changed. Low household incomes from CBNRM are unlikely to change attitudes of rural dwellers towards Western approaches to conservation. Communities must sustainably manage their natural areas as "green factories" for the multitude of natural resources they contain as a means of maximizing employment and thus household incomes, as well as meeting the often overlooked socio-cultural ties to wildlife and other natural resources, which may be as important as direct material benefits in assuring conservation of wildlife and its habitat. For CBNRM to be successful in the long-term, full devolution of ownership over land and natural resources must take place. In addition, as a means of relieving pressure on the rural resource base, this will require an urbanization process that creates a middleclass, as opposed to the current slums that form the majority of Africa‘s cities, through industrialization that transforms the unique natural resources of the subcontinent (e.g., strategic minerals, petroleum, wildlife, hardwoods, fisheries, wild medicines, agricultural products, etc.) in Africa.
Keywords: Development; conservation; industrialization; population; wildlife